2021
DOI: 10.1177/2333794x211050316
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Micronutrient Deficiency and Its Prevalence in Malnourished Pediatric Children as Compared to Well-Nourished Children: A Nutritional Emergency

Abstract: Pediatric populations from lower-income countries may experience a higher incidence of zinc deficiency, which may cause physical and neurological dysfunctions. This case control study aims to assess different levels of zinc between malnourished and well-nourished children. Our study included 108 participants, all children less than 12 years of age. Out of the 108, 54 were malnourished children (cases), while 54 were well nourished (control group) and were screened for zinc deficiencies. Zinc deficiencies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…These results are comparable to several other studies [ 21 , 23 , 24 ]. However, few studies found no gender-wise difference among children and adolescents in the case of Fe, Zn [ 25 , 26 ]. According to one report, countries with more than 25% of their population eating a zinc-deficient diet (plant-based diets) are in danger of acquiring zinc deficiency [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are comparable to several other studies [ 21 , 23 , 24 ]. However, few studies found no gender-wise difference among children and adolescents in the case of Fe, Zn [ 25 , 26 ]. According to one report, countries with more than 25% of their population eating a zinc-deficient diet (plant-based diets) are in danger of acquiring zinc deficiency [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings contradict Saudi studies that found no significant Se deficiency among normal growing children and adolescents [ 25 , 28 ]. A New Zealand study found that 22.9 percent of children had low serum Se values [ 26 ]. Interestingly, Al-Hussaini [2022] reported that among the low BMI category, 22% of children had Se deficiency [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In children who were recovering from malnutrition, there was a deficiency of copper, which is a vital metal required for various enzymes necessary for life [26]. Ahsan AK (2021) and their co-workers conducted a study that suggested a four-fold higher prevalence of zinc deficiency in cases of malnutrition compared to the control group [27]. Mayo-Wilson et al demonstrated a notable positive impact of zinc supplementation on both height and weight in children ranging from 6 months to 12 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The studies reported 54.2% of children and 37.1% preschool children to be zinc deficient. Several studies indicate that zinc deficiency results in poor growth in infants and children and depressed appetite (7,8). Zinc deficiency may also lead to impaired motor development in infants and thus can interfere with cognitive performance.…”
Section: Introductionmentioning
confidence: 99%